JUNIOR HIGH SCHOOL STUDENTS PERCEPTION TOWARD ENGLISH VIDEOS ON TIKTOK TO IMPROVE THEIR VOCABULARY MASTERY - PUTRI UTAMI KUSUMA WARDANI (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The aim of this study is to find out students perception on the use of TikTok Â in improving students vocabulary mastery. For the research design, the researcher used descriptive qualitative method. The researcher choose eight grade from one of junior high school in Malang. The procedure of this research involved one step, interview. The finding showed that Tiktok was considered very helpful by the participants because they used TikTok as a means to watch videos about vocabulary or educational videos. The participants said that they got some information or knowledge about vocabulary by watching videos on the Tikok. They also knew a lot about various content which consist of many random video including educational video. The participants said that by using Tiktok they could get some information or knowledge about vocabulary. The video are provide English vocabulary raise their motivation and their interest to know some new vocabulary.Â Keyword: Perception, Tiktok Videos, Vocabulary Mastery.Â